[3x/(x-2)-x/(x+2) ]*(x²-4)/x 乘法分配律 (a+b)*c=ac+bc
=[3x/(x-2)]*(x²-4)/x-[x/(x+2) ]*(x²-4)/x
=3(x+2)-(x-2)
=2x+8
[3x/(x-2)-x(x+2) ]*(x²-4)/x 通分
={[3x(x+2)-x(x-2)]/(x+2)(x-2)}*(x²-4)/x
=[(3x²+6x-x²+2x)/(x²-4)]*(x²-4)/x
=2x+8
方法一:通分
[3x/(x-2)-x(x+2) ]*(x²-4)/x
={[3x(x+2)-x(x-2)]/(x+2)(x-2)}*(x²-4)/x
=[(3x²+6x-x²+2x)/(x²-4)]*(x²-4)/x
=2x+8
方法二:乘法分配律
[3x/(x-2)-x/(x+2) ]*(x²-4)/x
=[3x/(x-2)]*(x²-4)/x-[x/(x+2) ]*(x²-4)/x
=3(x+2)-(x-2)
=2x+8
注:乘法分配律 (a+b)*c=ac+bc
方法一:
{3X/(X-2)-
X/(X+2)}·
(4-X2)/
X
={3(X+2)-
(X-2)}/(X-2)
(X+2)·{-
(X2
-4)}
=(3X+6-
X+2)
/(X-2)
(X+2)·{-
(X-2)
(X+2)}
=-(2X+8)
=-2X-8
方法二:
{3X/(X-2)-
X/(X+2)}·
(4-X2)/
X
={3(X+2)-
(X-2)}/(X2-4)·{-
(X2
-4)}
=(3X+6-
X+2)
/(X2-4)·{-
(X2-4)}
=-(2X+8)
=-2X-8
[3x/(x-2)-x/(x+2)
]*(x²-4)/x
乘法分配律
(a+b)*c=ac+bc
=[3x/(x-2)]*(x²-4)/x-[x/(x+2)
]*(x²-4)/x
=3(x+2)-(x-2)
=2x+8
[3x/(x-2)-x(x+2)
]*(x²-4)/x
通分
={[3x(x+2)-x(x-2)]/(x+2)(x-2)}*(x²-4)/x
=[(3x²+6x-x²+2x)/(x²-4)]*(x²-4)/x
=2x+8
-(X/2) - 3/2 (-4 + X^2)